Congenital cystic lesions of lung in the paediatric population: A 5-year single institutional study with review of literature - Shibsankar Barman; Kartik Chandra Mandal; Rajarshi Kumar; Sumitra Kumar Biswas; Madhumita Mukhopadhyay; Biswanath Mukhopadhyay (Wolters Kluwer Medknow Publications, 2015)
Background: The aim was to evaluate the clinical presentation, investigation modalities, operative management, pathology, outcome (morbidity and mortality) and short term follow-up of congenital cystic lesions of the lung. Materials and Methods: This is a retrospective study. Study period was 5 years (December 2008-November 2013) in the Department of paediatric surgery, Nil Ratan Sircar Medical College. Study population: Total number = 10 patients. Age range: 2 days-7 years. (Neonate-4). Male and female ratio = 1:1. Result: Among 10 cases of lung cyst four having congenital lobar emphysema, four having congenital pulmonary airway malformation, one sequestration and one teratoma. All patients have undergone surgical excision in terms of lobectomy or excision of the lesion. Post-operative histopathology confirmed the diagnosis. Recovery was uneventful. Conclusion: Although our experience is limited, operative management of lung cysts seems to be safe with rewarding results. However we are yet to encounter many of the other varieties of the cysts found in the lung, which may be associated with other congenital anomalies and have an impact on prognosis.